Aristocrats of Color : The Black Elite, 1880-1920 - Gatewood, Willard B., Jr. (Willard Badgett), 1931- (Book collections on Project MUSE., 2000)
Every American city had a small, self-aware, and active black elite, who felt it was their duty to set the standard for the less fortunate members of their race and to lead their communities by example. Professor Gatewood's study examines this class of African Americans by looking at the genealogies and occupations of specific families and individuals throughout the United States and their roles in their various communities. --from publisher description.